Construction and application of liver cancer models in vitro - Changmin Shao; Qingfei Zhang; Gaizhen Kuang; Qihui Fan; Fangfu Ye (Engineered Regeneration, 2022)
Primary liver cancer is the fifth most common malignancy and the third leading cause of cancer death worldwide. Although current advances in the treatment of liver cancer, the prognosis of this cancer remains unfavorable. Appropriate liver cancer model in vitro is an important way to study the pathogenesis and drug screening of liver cancer. This review provides a comprehensive summary and discussion on the construction and application of liver cancer models in vitro, in particular hepatocellular carcinoma (HCC). Specifically, after introducing the current methods or techniques for preparing 3D in vitro liver cancer models, this review summarizes the relevant applications of these liver cancer models in vitro, e.g. drug screening, personalized medicine, and other applications. In the end, this review discusses the advantages and disadvantages of the liver cancer models in vitro, and proposes future prospects and research directions.